Mental Models of Cause and Inheritance for Type 2 Diabetes Among Unaffected Individuals Who Have a Positive Family History. (March 2018) - Daack-Hirsch, Sandra; Shah, Lisa L.; Cady, Alyssa D.
Using the familial risk perception (FRP) model as a framework, we elicited causal and inheritance explanations for type 2 diabetes (T2D) from people who do not have T2D but have a family history for it. We identified four composite mental models for cause of T2D: (a) purely genetic; (b) purely behavioral/environmental; (c) direct multifactorial, in which risk factors interact and over time directly lead to T2D; and (d) indirect multifactorial, in which risk factors interact and over time cause a precursor health condition (such as obesity or metabolic syndrome) that leads to T2D. Interestingly, participants described specific risk factors such as genetics, food habits, lifestyle, weight, and culture as "running in the family." Our findings provide insight into lay beliefs about T2D that can be used by clinicians to anticipate or make sense of responses to questions they pose to patients about mental models for T2D.